Boda-bodas rule: Non-agricultural activities and their inequality implications in Western Kenya - Jann Lay; George Michuki M'Mukaria; Toman Omar Mahmoud (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
Diversification into non-agricultural activities in rural areas can be broadly classified as either survival-led or opportunity-led. The existence of these two types of non-agricultural activities implies a U-shaped relationship between the share of income derived from non-agricultural activities and household wealth as well as total household income. Survival-led engagement in non-agricultural activities would be inequality-decreasing through increasing the incomes of the poorer parts of the population and would reduce poverty. Opportunity-led diversification, by contrast, would increase inequality and have a minor effect on poverty, as it tends to be confined to non-poor households. Using data from a household survey conducted by ourselves in Western Kenya, we find the overall share of non-agricultural income in this very poor region to be important, but below the sub-Saharan African average. Multivariate analyses confirm the existence of both survival-led and opportunity-led diversification. Yet, the poverty and inequality implications of the differently motivated diversification strategies differ somewhat from our expectations. As expected, we find high-return activities to be confined to richer households, while both rich and poor households are engaged in low-return activities. Very poor households even appear to be excluded from the latter. Simple simulation exercises illustrate the inequality-increasing and very limited poverty effects of increases in high-return income, whereas increased low-return income shows substantial poverty reduction leverage. Our findings indicate that rural households do not only face asset constraints, but also very limited or relatively risky high-return opportunities outside agriculture.
Keywords: I31; O17; Q12; 330; Non-agricultural activities; Inequality; Income diversification; Dorfwirtschaft; Landwirtschaftlicher Kleinbetrieb; Diversifikation; Ländliches Einkommen; Einkommensverteilung; Kenia (West); Afrika südlich der Sahara